Effect of Potato virus Y Presence in Solanum tuberosum (Solanales: Solanaceae) and Chenopodium album on Aphid (Hemiptera: Aphididae) Behavior. Issue 3 (2nd April 2018) - Murphy, Alexzandra F; Rondon, Silvia I; Moreno, Aranzazu; Fereres, Alberto
Abstract: This study establishes the effect of Potato Virus Y (PVY; Potyvirus ) in potatoes, Solanum tuberosum L. (Solanales: Solanaceae) and in common-lambs' quarter Chenopodium album L. (Amaranthaceae) on Macrosiphum euphorbiae Thomas (Hemiptera: Aphididae) and Myzus persicae Sulzer (Hemiptera: Aphididae) behavior, host preference, transmission, and fitness under field and laboratory studies. In the field, several weeds, besides C. album, were collected, including: Sisymbrium altissimum L. (Brassicaceae), Erodium cicutarium L., Lactuca serriola L., Solanum sarrachoides Sendtner (Solanaceae), and S. dulcamara L. (Solanaceae). All weeds were serologically tested for the presence of PVY. From all weeds collected, 2.3 and 34% of C. album and S. sarrachoides, respectively, were PVY-positive. From those positive samples, 72% of the PVY found were PVY N ; the remaining 28% was PVY O . In addition, several aphid species were collected from those weeds: Ovatus crataegarious Walker, Macrosiphum euphorbiae (Hemiptera: Aphididae), Hyalopterus pruni Geoffroy (Hemiptera: Aphididae), Rophalosiphum madis Fitch, and 'others aphid' species were collected. The highest number of aphids were collected in E. cicutarium, followed by S. dulcamara, L. serriola, S. altissimum, and C. album . In laboratory studies, PVY-infected C. album does not induce the production of aphids. Moreover, M. persicae did not appear to have a strong preference for either healthy or PVY-infected potato plant, but they did develop a preference for infected plants after prolonged feeding. M. persicae and M. euphorbiae transmitted PVY from C. albu m to S. tuberosum, 44 and 37.5 % of the time. Future research should seek to identify not only other sources and prevalence of PVY in the field but vector relationships. In insect-pathogen complex continues to persist in solanaceous field crops around the world.